O pesquisador brasileiro, o acesso aberto e a CAPES: uma analise durkheimiana - Veiga, Viviane Santos de Oliveira; Silva, Cícera Henrique da; Neto, André Pereira (Cadernos BAD, 2014)
O pesquisador brasileiro, o acesso aberto e a CAPES: uma analise durkheimiana